Perancangan E-Commerce Berbasis OpenCart untuk Promosi dan Penjualan Produk Makanan Usaha Ikan Asin - Alfajri, Habib; Annas, Firdaus; Arya Winaldi, Deni (JOVISHE : Journal of Visionary Sharia Economy, 2023)
This article discusses the design of an e-commerce platform based on OpenCart to support the promotion and sales of food products, specifically focusing on salted fish businesses. The purpose of this study is to design a digital sales system that can enhance market reach, operational efficiency, and competitiveness of small businesses in the digital era. The initial condition shows that salted fish businesses still rely on traditional marketing methods, such as direct sales and word-of-mouth promotion, which have limitations in reaching a broader market and face competitiveness challenges with other business players. The ideal condition is an integrated e-commerce system that facilitates online promotion, digital transactions, and automated data recording. The research methodology involves needs analysis, system design and development using the OpenCart platform, as well as performance testing through implementation in small business groups. The designed system includes key features such as product cataloging, stock management, digital payment integration, and order tracking, which are tailored to meet the needs of small business operators. The results show that this platform effectively increases customer accessibility to products, accelerates transaction processes, and provides data-driven insights that can support strategic decision-making in businesses. The findings indicate that adopting technologies like OpenCart can significantly strengthen the competitiveness of traditional businesses through business process digitization. Furthermore, this platform provides opportunities for small businesses to easily connect with potential customers in various regions. The implications of this study include a model of technology adaptation for other small and medium enterprises (SMEs) with limited resources, as well as recommendations for developing additional features such as logistics integration and online payment systems to maximize the benefits of e-commerce for small businesses.